Adversity Quotient: Fenomena Fatherless Involvement dan Kecerdasan Sosial Emosional Anak Usia Dini - Silpiani, Mega; Wahyudin, Erik (Mulya Literasi Publishing, 2024)
This article is the result of research that examines the influence of fatherless involvement and social-emotional development on the adversity quotient of early childhood. The research method used is quantitative with multiple linear regression tests. This research was conducted among the people of Purwawinangun sub-district, Kuningan, West Java. The research results show that fatherlessness positively affects the adversity quotient. Social emotions positively impact the Adversity Quotient, and fatherless and Social emotional influence the Adversity Quotient. Lack of positive interaction with the father can result in children experiencing difficulties in developing life skills and social abilities, this can hurt the child's ability to survive and find solutions to every problem.